Shaping place identity through cultural storytelling: strategic communication in a small mountain city - Rahmanto, Andre Noevi; Fariza, Muhammad Rio (Frontiers in Communication, 2025)
City branding has become an important strategy for local governments, yet small and semi urban mountain regencies remain underexplored; this research examines how cultural storytelling functions as a form of strategic communication in shaping the city branding of Magetan Regency, East Java, Indonesia, using the City Brand Hexagon framework. The study employed a qualitative case study design, drawing on Focus Group Discussions (FGDs) with cross sector stakeholders and document analysis of regional planning documents, tourism programs, and promotional materials, with thematic analysis guided by the six dimensions of the City Brand Hexagon, namely Presence, Place, Potential, People, Pulse, and Prerequisites. The findings show that Magetan’s brand identity is constructed through a balanced articulation of these dimensions, integrating cultural narratives, local history, and natural tourism potential, which are visually embodied in the “Magetan Ngangeni” tagline and a logo that features Mount Lawu, the Lawu Starling, the keris, and natural motifs such as lakes and waterfalls. Overall, cultural storytelling based city branding operates not only as a promotional mechanism but also as a participatory communication process that negotiates place identity, fosters stakeholder co creation, and supports sustainable regional competitiveness for small mountain cities.